Pollen production, viability and in vitro pollen germination of different litchi (Litchi chinensis) genotypes - GUPTA, ALOK KUMAR; SINGH, MANVENDRA; MARBOH, EVENING S; NATH, VISHAL; VERMA, JAI PRAKASH (The Indian Journal of Agricultural Sciences, 2018)
Litchi (Litchi chinensis Sonn.) is one of the important commercial fruits of the subtropical region. Its short flowering period couple with narrow genetic base serves as the major constraints in litchi genetic improvement. Pollen are known to directly influence reproductive success and genetic structure of the plant population. In this study, we compare the pollen quantity per anther, viability and in vitro pollen germination of two types of male flower (M1 and M2) of four different litchi genotype, viz. Shahi, China, Bedana and Kasba. Pollen quantity was evaluated by blood count method while pollen viability was assessed using acetocarmine, 2, 3, 5-triphenyl tetrazolium chloride (TTC), 2, 5-diphenyl monotetrazolium bromide (MTT) and aniline blue-lectophenol staining methods. For germination test, different concentrations of sucrose, boric acid (H3BO3) and agar were used. Highest pollen quantity was observed in Shahi (5292) followed by China (5022), Kasba (4775), and Bedana (4186) in the pollen from M2 flower. Acetocarmine solution (1.0 %) was most suitable dye for pollen viability test. Staining results revealed that M2 pollen were more viable than M1. Among the different media concentrations, in vitro pollen germination medium containing 15 % sucrose + 100 ppm boric acid + 1.0% agar showed promising results. Further assessment of the germination potential, pollen from M1 and M2 flower were incubated at different temperature and duration. Highest germination rate was observed at 25oC with incubation period of 12 hr but maximum pollen tube growth occurs at 25oC for 24 hr. Pollen from M2 flower had significantly higher pollen quantity, viability and germination rate compared to pollen from M1flower. Preservation and conservation of M2 pollen with high viability and germination potential for adaptation to different climatic condition of this important litchi tree fruit.